Potentiostatic phase formation of β-CoOOH on pulsed laser deposited biphasic cobalt oxide thin film for enhanced oxygen evolution. Issue 44 (27th October 2017) - Mathankumar, M.; Anantharaj, S.; Nandakumar, A. K.; Kundu, Subrata; Subramanian, B.
Abstract : Atomic layer fabrication of biphasic spinel Co3 O4 and CoO on an FTO substrate through pulsed laser deposition was achieved and the fabricated Co x O y interface was found to undergo tremendous surface construction under an applied potential which eventually increased the activity by reducing the overpotential by 55 mV. Abstract : Enhancing the electrocatalytic water oxidation activity of an electrocatalyst by altering its solid state properties at the electrode/electrolyte interface is a promising way to minimize the energy loss in water splitting. Atomic layer thin films of biphasic spinels Co3 O4 and CoO were fabricated through pulsed laser deposition (PLD) and examined for the oxygen evolution reaction (OER). During this process, the biphasic thin film interface of cobalt oxides underwent significant activation after prolonged potentiostatic electrolysis at 1.59 V vs. RHE with pronounced enhancement in its OER activity. The biphasic thin film interface of cobalt oxides required 372 ± 5 mV to drive 10 mA cm −2 which was reduced by 55 mV after activation. The associated lower Tafel slope (55 mV dec −1 ) implies better kinetics on the activated thin film interface of cobalt oxides. This indicated that the thin film of cobalt oxides must have undergone significant surface reconstruction at the interface. To find out the same, a set of detailed pre- and post-activation material characterization studies were carried out where the results have evidenced that there had been a dominant formation of β-CoOOH along with some Co(OH)2 and KCoO2 as a result of the phenomenon of electrochemical phase (ECP) formation under potentiostatic/galvanostatic activation conditions. A comparative study under identical conditions with the state-of-the-art OER electrocatalyst RuO2 had revealed that the biphasic thin film interface of cobalt oxides had nearly parallel activity before activation and better activity after the construction of β-CoOOH along with some Co(OH)2 and KCoO2 via potentiostatic surface reconstruction of the catalytic interface.